Therapeutic uses of plants of genus Blepharis - a systematic review - S.VIJAYALAKSHMI; K.G. KRIPA (International Journal of Pharma and Bio Sciences, 2016)
Nature has been a source of medicinal agents for thousands of years and a remarkable number of modern drugs have been isolated from natural sources. Higher plants, as sources of medicinal compounds, have continued to play a dominant role in the maintenance of human health since ancient times. Over 50% of all modern clinical drugs are of natural product origin and play an important role in drug development programs in the pharmaceutical industry. Blepharis is an Afro-asiatic genus comprising 129 species, belonging to the family Acanthaceae, widely distributed in arid and semi-arid habitats. Some of the species include B. attenuata Napper, Blepharis edulis, B. sindica, and B. maderaspatensis. These plants exhibit a wide range of pharmacological activities including antioxidant, anti-inflammatory, anti-arthritic, antimicrobial, antifungal, anti-ulcer and cytotoxic activities. Some established pharmacological activities of these plants have been discussed in this article. The plant species being widely distributed can be used as an alternative to the conventional medicines. Hence, there is a need to know the feasibility of using extracts and bioactive compounds derived from such plants for the control of chronic diseases as claimed by traditional healers.